Mongolia : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2001)
Mongolia has made great strides in fostering a market economy and promoting macroeconomic stability under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors welcomed this step, and stressed the need to improve economic governance, fiscal and monetary policies, and accelerate structural reforms. They appreciated the fiscal transparency and accountability, realistic budgeting, better treasury management, and the privatization and energy sector reform. They agreed that the government's reform program merits the support of the international community, and approved the request for a three-year arrangement under the PRGF.